Personalized exercise programs in oncology - Saleh, Ahmed Yakdhan; Shareef, Abdulkareem; Bishoyi, Ashok Kumar; Jyothi, S. Renuka; Panigrahi, Rajashree; Pargaien, Amrita; Garg, Gunjan; Hafizova, Mashkhura; Sameer, Hayder Naji; Yaseen, Ahmed; Athab, Zainab H.; Adil, Mohaned (Oncology Reviews, 2025)
Exercise is increasingly recognized as a safe and effective adjunct therapy across the cancer care continuum, offering improvements in physiological function, psychological wellbeing, and treatment outcomes. However, conventional one-size-fits-all exercise prescriptions often fall short of addressing the diverse needs of cancer patients, who differ significantly in tumor type, treatment modality, baseline fitness, and comorbidities. Personalized exercise programs offer a tailored, evidence-informed approach that enhances safety, adherence, and clinical benefits. This narrative review synthesizes the current literature on the physiological, psychological, and oncological impacts of exercise in cancer care, emphasizing the rationale, methodologies, and emerging tools for individualized exercise prescriptions. Integration of such programs into oncology practice requires standardized assessments, interdisciplinary collaboration, and digital infrastructure, with a focus on addressing barriers to implementation and ensuring equitable access. Personalized exercise programs have the potential to improve patient outcomes and survivorship experiences across diverse cancer populations.